Lacunae Iuris dalam Hukum Kebebasan Beragama di Indonesia - Alexius Andang Listya Binawan (Faculty of Theology Duta Wacana Christian University, 2023)
AbstractBy examining the lacunae iuris, or legal “holes,” in the theoretical sense of Indonesian law on religious freedom, this article falls short of normative juridical research. In particular, the seven points linked tothe law of religious freedom—the meaning of religion, the meaning of divinity, the meaning of freedom, its contents, its subject, its boundaries, and the role of the state—will be examined in more depth in this article. This research employs the legal approach method, contrasting ideas of Indonesian laws with international law, which is also acknowledged as a fundamental component of Indonesian law. When these seven points of the law of religious freedom are compared, it becomes clear that Indonesia’s law of religious freedom has some significant gaps, particularly in the areas where freedom is still restricted and where it relates to concepts of divinity and religion that are also severely constrained. The findings of this research may serve as the foundation for initiatives aimed at enhancing Indonesia’s freedom law and ensuring greater justice and certainty. AbstrakArtikel ini adalah sebuah penelitian yuridis normatif dengan mencermati lacunae iuris atau ‘lubang’ hukum dalam arti teoretis dari hukum kebebasan agama di Indonesia. Tujuan artikel ini adalah melihat lacunae iuris itu secara lebih detail, terutama yang tampak dalam tujuh pokok terkait hukum kebebasan beragama itu, yaitu makna agama, makna ketuhanan, makna kebebasan, isinya, subjeknya, pembatasannya, dan peran negara. Metode penelitian ini adalah statute approach, dengan cara membandingkan isi (notions) hukum yang berlaku di Indonesia dengan hukum internasional yang juga diakui sebagai bagian integral hukum. Hasil perbandingan dari isi dari tujuh pokok hukum kebebasan beragama, lacunae iuris hukum kebebasan beragama di Indonesia tampak sangat jelas, terutama dalam isi kebebasan yang masih sempit, terkait dengan konsep tentang ketuhanan dan konsep tentang agama yang sangat terbatas. Hal ini bisa menjadi dasar untuk upaya perbaikan hukum kebebasan di Indonesia agar bisa memberi kepastian dan keadilan yang lebih baik.